Nurse lecturers' experiences with online teaching during the pandemic at a public university in Gauteng, South Africa - Andile G. Mokoena-de Beer; Sophy M. Moloko (AOSIS, 2022)
Background: Nurses' training has been mostly face-to-face in the South African context. This mode of delivery was linked to producing nurses who are critical thinkers, problem solvers and competent in practical skills. However, the emergence of coronavirus disease 2019 (COVID-19) accelerated the need for online teaching in nursing. Nurse lecturers were forced to teach online in order to save the academic project, despite concerns about the competencies and calibre of nurses produced through online teaching. Objectives: This study aimed to explore and describe nurse lecturers' experiences with online teaching during the COVID-19 pandemic at a public university in Gauteng, South Africa. Method: A qualitative, exploratory design was utilised. Six nurse lecturers - two males and four females - were purposefully selected to participate in this study. Data were collected through in-depth interviews to obtain rich, thick descriptions from the nurse lecturers who experienced online teaching. Content analysis was used to analyse the data. Results: Five themes emerged as, (1) challenges related to the learner management system; (2) challenges related to competency; (3) factors out of the span of control of the lecturer; (4) indirect benefits of online teaching; and (5) recommendations to facilitate the smooth delivery of online teaching. Conclusion: The findings established that nurse lecturers experienced challenges when teaching online, which resulted in frustrations and discomfort for lecturers. Contribution: The study revealed the challenges nurse lecturers faced while teaching online. It highlights the need for nurse lecturers to be trained and supported to enhance online teaching and learning.